KANDUNGAN FOSFOR DALAM TANAH PADA TEGAKAN JATI (Tectona grandis), MAHONI (Swietenia macrophylla) DAN LEGARAN (Alstonia spectabillis R.Br) DI HUTAN PENDIDIKAN WANAGAMA I - , EKO SINGGIH KURNIAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Soils in Wanagama 1 education forest Gunungkidul is degraded, it is characterized by a thin solum and rocky. rehabilitation efforts by planting a pioneer plant is an important factor for handling the criticality wanagama I education forest . These plants affect the development of land that is characterized by the more solum, the more soil organic and more impact on the adequacy of water and nutrients for plant growth. the efforts to determine the content of organic matter and nutrients need to be done, one of the way is creating a permanent sample plots. the plots are intended as a basic for research and development in terms of both standing and the existing environment in Wanagama 1 Education forest. One of the things that can be studied is the nutrient content of phosphorus (P). The purposes of this study are determining the nutrient content of phosphorus (P-total) on the ground and finding out the initial data influence the nutrient content of phosphorus (P-total) in the area of Teak (Tectona grandis) plots 6 and 7, Mahogany (Swietenia macrophylla) plot 16 and Legaran (Alstonia spectabillis R.Br) plot 18. Research methods in the field of high measurement, diameter and soil sampling on the 4th level of depth (0-10 cm, 10-20 cm, 20-30 cm and 30-50 cm), whereas in the laboratory analysis phosphorus (P-total) with the method of destruction. The results showed the nutrient content of phosphorus (P-total) in each stands is different: Teak plot 6 at 0.019% (very low), Teak plot 7 at 0.03% (low), Mahogany plot 16 at 0.026% (very low) and Legaran plot 18 at 0.036% (low). The mean of diameter Teak plot 6 at 1,38 cm, Teak plot 7 at 1.6 cm, Mahogany plot 16 at 0.59 cm and Legaran plot 18 at 4.59 cm. The mean of height teak plot 6 at 0.87 m, Teak 7 plots at 0.91 m, Mahogany plot 16 at 0.5 m and Legaran plot 18 at 4.82 m. The survival rate of the teak plot 6 was 77.35% , Teak plot 7 at 65.31%, Mahogany plot 16 by 93.53% and Legaran plot 18 at 89.05%.